Cell type-specific chromatin accessibility analysis in the mouse and human brain. Issue 2 (1st February 2022) - Rocks, Devin; Jaric, Ivana; Tesfa, Lydia; Greally, John M.; Suzuki, Masako; Kundakovic, Marija
ABSTRACT: The Assay for Transposase Accessible Chromatin by sequencing (ATAC-seq) is becoming popular in the neuroscience field where chromatin regulation is thought to be involved in neurodevelopment, activity-dependent gene regulation, hormonal and environmental responses, and pathophysiology of neuropsychiatric disorders. The advantages of using ATAC-seq include a small amount of material needed, fast protocol, and the ability to capture a range of gene regulatory elements with a single assay. With increasing interest in chromatin research, it is an imperative to have feasible, reliable assays that are compatible with a range of neuroscience study designs. Here we tested three protocols for neuronal chromatin accessibility analysis, including a varying brain tissue freezing method followed by fluorescence-activated nuclei sorting (FANS) and ATAC-seq. Our study shows that the cryopreservation method impacts the number of open chromatin regions identified from frozen brain tissue using ATAC-seq. However, we show that all protocols generate consistent and robust data and enable the identification of functional regulatory elements in neuronal cells. Our study implies that the broad biological interpretation of chromatin accessibility data is not significantly affected by the freezing condition. We also reveal additional challenges of doing chromatin analysis on post-mortem human brain tissue. Overall, ATAC-seq coupled with FANS is a powerful method to capture cell-type-specific chromatin accessibility information in mouse and human brain. Our study provides alternative brain preservation methods that generate high-quality ATAC-seq data while fitting in different study designs, and further encourages the use of this method to uncover the role of epigenetic (dys)regulation in the brain.